1988
DOI: 10.4141/cjps88-043
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Alternating Freeze and Thaw Stresses in Wheat, Rye, Triticale and Foxtail Barley

Abstract: One local biotype of foxtail barley (Hordeum jubatum), seven cultivars of rye (Secale cereale), three cultivars of triticale (X Tritico-secale) and 14 cultivars of wheat (Triticum aestivum) were tested for their resistance to alternating freeze and thaw stresses in an unheated greenhouse in winter. Foxtail barley maintained 95% survival after five freeze-thaw cycles. Most rye cultivars were also significantly superior to all other cereals. Survival of all wheat and triticale cultivars ranged from 10 to 50% aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In fact, although not lethal, extracellular ice formation can cause mechanical stresses from cell and tissue displacement, cellular dehydration and collapse, so that the following rehydration and expansion may be damaging (Guy, 2003;Xin and Browse, 2000). Furthermore, the conditions typical of thawing may result in an excessive plant hydration (Bolduc et al, 1988) and the relatively warm periods associated with a thawing event may enhance respiration and induce plant dehardening, thus reducing plant resources and increasing plant susceptibility to snow molds and low temperature damage (Nakajima and Abe, 1994). Finally, in the presence of snow, the occurrence of rain over snow and freeze-thaw cycles creates conditions that are conducive to soil heaving, injuries to root tissues and ice encasement.…”
Section: Damage Induced By Freeze-thaw Cyclesmentioning
confidence: 97%
See 3 more Smart Citations
“…In fact, although not lethal, extracellular ice formation can cause mechanical stresses from cell and tissue displacement, cellular dehydration and collapse, so that the following rehydration and expansion may be damaging (Guy, 2003;Xin and Browse, 2000). Furthermore, the conditions typical of thawing may result in an excessive plant hydration (Bolduc et al, 1988) and the relatively warm periods associated with a thawing event may enhance respiration and induce plant dehardening, thus reducing plant resources and increasing plant susceptibility to snow molds and low temperature damage (Nakajima and Abe, 1994). Finally, in the presence of snow, the occurrence of rain over snow and freeze-thaw cycles creates conditions that are conducive to soil heaving, injuries to root tissues and ice encasement.…”
Section: Damage Induced By Freeze-thaw Cyclesmentioning
confidence: 97%
“…The latter may cause additional stresses to the plants, such as anoxia and the buildup of disruptive concentrations of ethanol, CO 2 , and lactic acid (Andrews, 1996). Indeed, Bolduc et al (1988) showed that hardened winter wheat plants were severely damaged and their survival rate drastically reduced when exposed to three or more freeze-thaw cycles (each freeze-thaw cycle consisted of 14 days, with the first 7 days of freezing temperatures).…”
Section: Damage Induced By Freeze-thaw Cyclesmentioning
confidence: 97%
See 2 more Smart Citations